Stone Artefacts from Late Roman Occupation Phases in Nea Paphos - Pawlik, Karolina (Études et Travaux, 2018)
Nea Paphos was a vibrant city in Roman Cyprus. Much information about the history and the inhabitants of the urban centre came to light through extensive excavations, which started at the site in the 1960s. The Hellenistic and Roman period has been widely studied and examined, but our knowledge of late Roman Paphos still remains quite modest. The purpose of this paper is to provide a better understanding of the late Roman phases of occupation, especially of the squatters’ activities in Paphos, through the analysis of stone objects, mainly grinding and milling stones and other worked stone, which are associated with this period.